1975
DOI: 10.1029/ja080i004p00694
|View full text |Cite
|
Sign up to set email alerts
|

Group travel time for proton whistlers in the ionosphere

Abstract: In this communication a theoretical relation is derived for the group travel time of the proton whistlers to reach the satellite from their place of occurrence. The expression for the group travel time contains two terms. The first term is the dominant term and is inversely proportional to (Ω ‐ ω)1/2, where Ω and ω are the proton gyrofrequency and the wave frequency, respectively. The contribution from the second term, which is inversely proportional to (Ω ‐ ω)7/2, is about 10% of the first term. It is shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1976
1976
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…In this case, the mathematical analysis is very complicated and a WKB method must be used (Budden 1961;Khan & Paul 1977). Consideration of thermal effects (Singh & Tolpadi 1975;Singh, Tiwari & Tolpadi 1976) and the streaming velocity of the plasma species, including newly formed ions (Das & Sur 1986), is also likely to lead to interesting results regarding nonlinear effects in whistlers.…”
Section: Some Concluding Remarksmentioning
confidence: 99%
“…In this case, the mathematical analysis is very complicated and a WKB method must be used (Budden 1961;Khan & Paul 1977). Consideration of thermal effects (Singh & Tolpadi 1975;Singh, Tiwari & Tolpadi 1976) and the streaming velocity of the plasma species, including newly formed ions (Das & Sur 1986), is also likely to lead to interesting results regarding nonlinear effects in whistlers.…”
Section: Some Concluding Remarksmentioning
confidence: 99%
“…The propagation of ion-cyclotron whistlers has been extensively studied since Smith et al [ 1964] first observed the proton whistlers recorded in the VLF receivers aboard the Alouette 1 and lnjun 3 satellites [Gurnett et al, 1965;Barrington et al, 1966;Gurnett and Rodriguez, 1970;Smith, 1970;Rodriguez and Gurnett, 1971;Wang, 1971;Chan et al, 1972;Jones, 1969Jones, , 1972Fijalkow et al, 1973]. The observed characteristic features of proton whistlers have been used by a number of workers to estimate some of the parameters in the ionosphere [Gurnett et al, 1965;Shawhah and Gurnett, 1966;Gurnett and Shawhah, 1966;Gurnett and Brice, 1966;Lucas and Brice, 1971].…”
Section: Introductionmentioning
confidence: 99%
“…All these theoretical studies are based on the theory of the propagation of electromagnetic waves in a cold multicomponent magnetoplasma developed by Smith and Brice [1964] and Gurnett et al [1965]. Singh and Tolpadi [1975] Because of their thermal motion some protons will absorb energy from the wave by cyclotron damping if the Doppler-shifted wave frequency is equal to their gyrofrequency. The rate at which wave energy is absorbed depends upon the number of protons that see the wave at their gyrofrequenCy.…”
Section: Introductionmentioning
confidence: 99%